Biopreservation of Pinus roxburghii and Bombax ceiba Using Aqueous Extract of Acorus calamus - Dhiman, B.; Dutt, B.; Somthane, Y. Y.; Heena (International Journal of Economic Plants, 2018)
Due to biological origin, wood is one of the most complex constructions materials and has affinity for moisture which can lead to biological deterioration. Biological damage to wood and wood products is mainly caused by the mould, stain, decay fungi, and insects such as beetles and termites. Therefore, wood preservation is required after harvesting to reduce attack by wood deteriorating agents. Development of low environmental impact technologies for the elimination of biological damage is one of the vital goals of wood protection industry. In the present study, effect of Acorus calamus extract on fungal growth was tested on wooden samples of Pinus roxburghii and Bombax ceibaat different concentrations.